INTERNALISASI NILAI TASAMUH DALAM PEMBINAAN KARAKTER SANTRI DI PONDOK MBURI WONG BODHO MBORO MENGANTI GRESIK - Sofyan Maulana; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Pondok Mburi Wong Bodho is a rehabilitation cottage and also accommodates all people who experience problems in their lives, Gus Khoiri is the caretaker of Pondok Mburi Wong Bodho who directly guides the students with advice and activities which encourage goodness. The principle that is built in the cottage is